Analysis of Raw Material Inventory Control to Achieve Cost Efficiency at PT Delapan Jaya Perkasa Garmen - Amir Amir; Rahmatul Ahya; Maria Pus pita Sari (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
PT Eight Jaya Perkasa Garmen is a company operating in the garment sector from Sragen, the products produced are trousers, shorts, shirts, suits, uniforms and so on. The problem that emerged at PT Empat Jaya Perkasa Garmen was the late supply of raw materials. Delays in the supply of raw materials result in the production process stopping. Control of raw materials is a solution to overcome this problem. Raw material inventory control is expected to be able to control raw materials so that the production process does not stop. The inventory costs incurred by PT Empat Jaya Perkasa Garmen for the procurement of raw materials can also be said to be quite high, this occurs because the purchase of raw material supplies is only based on habit. Therefore, in purchasing raw material procurement, you must first determine the raw material procurement policy using inventory models that are appropriate to the problems that are first analyzed using the EOQ method. This research aims to determine the raw material inventory control carried out by PT Empat Jaya Perkasa Garmen, and to find out how the Economic Order Quantity (EOQ) method can increase the efficiency of raw material inventory costs. From the results of calculations that have been carried out by comparing current policies in force. in companies using the EOQ method, it can be concluded that using the EOQ method the results are more efficient. This can be seen by the average purchase amount of 257,608 yards per order with a total order of 12 times a year and inventory costs of IDR 21,286,432, whereas when using the EOQ method the number of orders is 1,142,158.88 yards with a number of orders of 3 times a year. The total costs incurred are IDR 9,137,271.06. To anticipate undesirable things related to raw material supplies, the EOQ method advises the company to provide a safety stock of 14,781.36 yards and order materials again when the raw materials total 12,880.4 yards.